Distributed teams: challenges and opportunities - M. V. Orlova; I. Yu. Aleksandrova (Вестник университета)
A  geographically dispersed workforce poses new challenges for managers, which shift the focus from project management to managing distributed project teams. Adapting the company and its management to this evolution in the workplace, it is necessary to create an  environment in which remote team members interact productively. Distributed work requires operational flexibility from companies, which is characterised by  greater susceptibility to changes in their markets, to new emerging customer requirements and new competitive threats. The article is devoted to the identification of factors contributing to the transition of companies to the distributed workforce, the advantages of this type of work, and the difficulties that companies will face.